FATIGUE LIFE PREDICTION FOR ROW ANGULAR CONTACT BALL BEARINGS UNDER THERMO-MECHANICAL COUPLING BASED ON FEM - JIN Yan; LIU ShaoJun; JIANG YuXiao (Jixie qiangdu)
The effect of thermo-mechanical coupling was considered in order to obtain the fatigue life of spilt torque transmission row angular contact ball bearings in helicopter. Based on the L-P fatigue life and Hertz contact theory,an mathematical model was established with the combination of Goodman formula,material P-S-N curves and EM modify rule. The friction calorific effect was calculated and the convective heat tranfer coefficient was determined. Then the steady thermal analysis was conducted and the steady maximum temperature under different radial forces and rotate speeds was discussed. Finally the bearing fatigue life was investigated under the effect of thermo-mechanical coupling. The results show that the fatigue life decrease obviously with the operationg temperature raising,so the effect of frictional heating on fatigue life can’t be neglected.